2021
DOI: 10.1021/acs.jctc.1c00354
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Energetics of Dye-Sensitized NiO Interfaces in Water from Ab Initio MD and Large-Scale GW Calculations

Abstract: The energy-level alignment across solvated molecule/semiconductor interfaces is a crucial property for the correct functioning of dye-sensitized photoelectrodes, where, following the absorption of solar light, a cascade of interfacial hole/electron transfer processes has to efficiently take place. In light of the difficulty of performing X-ray photoelectron spectroscopy measurements at the molecule/solvent/metal−oxide interface, being able to accurately predict the level alignment by first-principles calculati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 128 publications
2
4
0
Order By: Relevance
“…First, no spontaneous dissociation of water molecules was observed on the surface, in contrast to what was observed during the DFT-MD simulation of hydrated NiO surfaces by some of us, confirming that water dissociation requires a rather large activation energy on the (001) WO 3 surface. Moreover, the molecular mechanisms involved in the adsorption of the water molecules were roughly the same as those predicted at 0 K. The first 8 water molecules were coordinated to the five-coordinated surface W 5c atoms with an average O w –W 5c bond length of 2.38 Å.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…First, no spontaneous dissociation of water molecules was observed on the surface, in contrast to what was observed during the DFT-MD simulation of hydrated NiO surfaces by some of us, confirming that water dissociation requires a rather large activation energy on the (001) WO 3 surface. Moreover, the molecular mechanisms involved in the adsorption of the water molecules were roughly the same as those predicted at 0 K. The first 8 water molecules were coordinated to the five-coordinated surface W 5c atoms with an average O w –W 5c bond length of 2.38 Å.…”
Section: Resultssupporting
confidence: 60%
“…Given these appealing advantages as a standalone or combined photocatalyst in various heterojunctions, WO 3 has been the subject of many experimental and theoretical studies in recent years. In particular, the solid/liquid interfacial properties, crucial for the efficiency of photocatalytic processes, have been theoretically investigated in the case of the WO 3 /water interface. ,, Previous computational studies have indeed addressed the fundamental understanding of the adsorption of water molecules on the γ-(001) surface [hereafter indicated as (001)]. ,,, Most of the reported studies have shown that water adsorbs preferentially in a molecular (undissociated) form since under-coordinated W atoms at the (001) surface are Lewis acids able to coordinate a water molecule …”
Section: Introductionmentioning
confidence: 99%
“…The energetics reported in this work are based on the total energies and orbital levels obtained by a GGA functional (PBE) corrected by a Hubbard term for the Ni d-orbitals. We are aware that the accuracy of this approach has some limitations and might be cured by many-body perturbation theories as shown, for example, in refs and . Nevertheless, we believe that our results are sufficiently accurate for the conclusions drawn in this work.…”
Section: Discussionmentioning
confidence: 99%
“…[6,[43][44][45] Over the last decades, ab initio investigations have been proven to be a valuable tool for getting atomistic insights into the grafting mechanism of molecular sensitizers onto semiconductor slabs, supporting experiments in optimizing the structure and charge generation properties of dye-semiconductor interfaces and providing fundamental understandings of the relevant phenomena governing the DSSCs functioning. [5,37,39,41,[46][47][48][49][50][51][52][53][54][55][56][57][58] Nevertheless, while a large number of theoretical works have addressed the dye adsorption on the TiO 2 surfaces (see for instance refs. [37,59], and references therein), only a few computational studies have appeared so far on the adsorption of anchoring groups or dyes on p-type semiconducting surfaces.…”
Section: Doi: 101002/pssb202200611mentioning
confidence: 99%